UPAYA PEMERINTAH DAERAH DALAM PENANGANAN KEMISKINAN DI KABUPATEN MAROS - Sakir, Ahmad Rosandi (Jurnal Ilmu Administrasi Negara, 2024)
This research aims to delve into, uncover, and analyze the steps and efforts undertaken by the Local Government of Maros Regency in addressing poverty. The applied research method is qualitative, utilizing a descriptive approach to gain a deeper understanding of the reality under investigation. Data are obtained through observation, in-depth interviews, and analysis of documents and archives, employing qualitative analysis techniques. The research results highlight two main aspects. Firstly, the efforts of the Local Government of Maros Regency in poverty alleviation are focused on the roles of the Department of Social Affairs, Manpower, and Transmigration, as well as the Department of Cooperatives, Industry, and Trade. They implement strategic programs, including the Family Hope Program (PKH), the Empowerment Program for the Poor (KUBE-FM), and the Empowerment Program for Micro, Small, and Medium Enterprises (UMKM). PKH is focused on social assistance, KUBE-FM aims to empower joint business groups of the poor, and the empowerment of UMKM serves as a local economic strategy. Secondly, the implementation of these programs is influenced by specific factors. Supportive factors include high commitment from relevant agencies, good coordination among various parties, internal motivation, and an integrated organizational structure. On the other hand, inhibiting factors involve the lack of understanding among impoverished communities regarding potential sanctions, budget limitations, low-quality human resources, obstacles in group member relationships, and a lack of skills among UMKM actors. Identifying these factors provides a more comprehensive understanding of the complexity of poverty alleviation in Maros Regency and serves as a foundation for improving policies and implementation strategies in the future.